2003
DOI: 10.1046/j.1365-2958.2003.03366.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron and contact with host cells induce expression of adhesins on surface of Trichomonas vaginalis

Abstract: SummaryThe proteins AP65, AP51, AP33 and AP23 synthesized by Trichomonas vaginalis organisms in high iron play a role in adherence. Multigene families encode enzymes of the hydrogenosome organelles, which have identity to adhesins. This fact raises questions regarding the compartmentalization of the proteins outside the organelle and about the interactions of adhesins with host cells. Data here demonstrate the presence of the proteins outside the organelle under high-iron conditions. Fluorescence and immunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
197
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(204 citation statements)
references
References 74 publications
(149 reference statements)
7
197
0
Order By: Relevance
“…Here, major effects were observed by scanning electron microscopy where large intercellular spaces were seen after parasite-cell interaction. Similar observations were previously tional complex of different cell lines takes place when they are submitted to several conditions, including removal of calcium [44][45][46]. Several other changes are associated with such disruption as (1) loss of membrane association of the junctional complex-associated proteins; (2) a loss of TJ strands, visualized in freeze-fracture replicas; (3) a decrease in the TER; and (4) a dramatic increase in transepithelial permeability to tracers.…”
Section: Discussionsupporting
confidence: 86%
“…Here, major effects were observed by scanning electron microscopy where large intercellular spaces were seen after parasite-cell interaction. Similar observations were previously tional complex of different cell lines takes place when they are submitted to several conditions, including removal of calcium [44][45][46]. Several other changes are associated with such disruption as (1) loss of membrane association of the junctional complex-associated proteins; (2) a loss of TJ strands, visualized in freeze-fracture replicas; (3) a decrease in the TER; and (4) a dramatic increase in transepithelial permeability to tracers.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, iron controls the expression of hydrogenosomal proteins such as pyruvate : ferredoxin oxidoreductase and ferredoxin (Gorrell, 1985), and virulence genes, such as those encoding some of the T. vaginalis adhesin proteins (Lehker et al, 1991;Engbring et al, 1996;Alderete et al, 1998;García et al, 2003). Tsai et al (2002) identified an iron-responsive promoter in the ap65-1 gene which could be involved in the transcriptional regulation of some of these genes.…”
Section: Introductionmentioning
confidence: 99%
“…At least one bovine T. foetus and five functionally diverse T. vaginalis adhesin proteins, named on the basis of their molecular weights ( T. foetus : Tf190; T. vaginalis : AP120, AP65, AP51, AP33, AP23) have been identified 48, 49, 56, 57. A direct relationship exists between cellular adherence and the abundance of adhesin proteins that remain bound to vaginal epithelial and HeLa cell surfaces after interaction with trichomonads 49, 58, 59. Isolates devoid of adhesins or treated with antiadhesin antibodies become nonadherent 58.…”
Section: Pathogenesis Of Trichomonosismentioning
confidence: 99%
“…Cysteine proteases mediate efficient adhesion of T. vaginalis to HeLa cells and vaginal epithelial cells in vitro 66. In bovine T. foetus , the role of cysteine proteases as adhesion proteins has not been investigated directly but is suggested by studies in a mouse model of venereal trichomonosis in which inhibition of trichomonad cysteine protease activity resulted in decreased genital colonization 58. At least 23 and 15 different cysteine proteases have been identified in T. vaginalis and bovine T. foetus , respectively 60, 67, 68, 69, 70.…”
Section: Pathogenesis Of Trichomonosismentioning
confidence: 99%